Metabolic rates and the energetic cost of external tag attachment in juvenile blacktip sharks Carcharhinus limbatus. Issue 2 (21st September 2018) - Lear, Karissa O.; Gleiss, Adrian C.; Whitney, Nicholas M.
Abstract : This study reports on the metabolic rate of the blacktip shark Carcharhinus limbatus and the energetic costs of external tag attachment. Metabolic rates, swimming speed and tail‐beat ( B T ) frequency were measured in a static respirometer with untagged animals and animals equipped with a small data logger. Tagged sharks showed significantly higher routine oxygen consumption and lower swimming speeds than untagged animals, indicating that tagging significantly affected the swimming efficiency and energetic requirements in these small sharks, and that these effects must be accounted for when interpreting telemetry data from free‐ranging individuals.